2015
DOI: 10.1002/tesj.229
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Experienced by Japanese Students With Oral Communication Skills in Australian Universities

Abstract: Due to ever-increasing demands to acquire effective communicative abilities in the English language, increasing numbers of international students choose to study in Western tertiary institutions; however, they frequently encounter difficulties in performing satisfactorily in English. This study aims to identify specific challenges that Japanese students face with oral communication skills while studying in Australian universities. Results from questionnaire data collected from 33 undergraduate and postgraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Feeling pressure to get to a diagnosis quickly, thus disregarding the diagnostic process was also considered as a potential student-centred obstacle to clinical reasoning development. Challenges faced by international students in regards to oral communication have been noted in other studies such as one performed by Yanagi and Baker (2016). Respondents in this study had most difficultly leading group discussions and speaking up in class discussions.…”
Section: Theme 4: Obstacles For Curricular Integration and Vertical Asupporting
confidence: 50%
See 2 more Smart Citations
“…Feeling pressure to get to a diagnosis quickly, thus disregarding the diagnostic process was also considered as a potential student-centred obstacle to clinical reasoning development. Challenges faced by international students in regards to oral communication have been noted in other studies such as one performed by Yanagi and Baker (2016). Respondents in this study had most difficultly leading group discussions and speaking up in class discussions.…”
Section: Theme 4: Obstacles For Curricular Integration and Vertical Asupporting
confidence: 50%
“…Student-centred disadvantages include the stress the exam generates in most students (Davis and Karunathilake, 2005, Joughin, 2010, Joughin et al, 2012, it is possible that some students' performances were affected by anxiety and not reflective of their true capabilities. We have a reasonable proportion of students for whom English is a second language in our cohorts and it is possible that at least some of these would have been disadvantaged by language and other cultural barriers (Yanagi and Baker, 2016). We attempted to minimise the anxiety associated with the exam by encouraging students to practice verbalising from the beginning of the year and providing many opportunities to practice in what should have been a relatively non-stressful environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1;Januari 2019. ISSN: 2337EISSN : 2337-7593 familiarize the students with the system of exam-based assessment orientation implemented in most of Asian country, including Indonesia (O"Donnell, 2005;Pritchard & Maki, 2006 as cited in (Yanagi & Baker 2015), rather than the system which is referring to the operation of the high level of thinking hierarchy to train them activate their thinking skills.…”
Section: Indonesia Master Of Education Student's Perceptions Of Theirmentioning
confidence: 99%
“…For example, a negative atmosphere in the classroom, where there are tense relations between students, can result in learners' reluctance to express their ideas verbally. This is illustrated in Yanagi and Baker's (2016) study which found that one of the most significant inhibitors of OC in English classes for Japanese students is the "fear of losing face" in front of their peers. Besides, in some circumstances, speaking English in a Japanese context might be considered as "showing off" (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%